2017
DOI: 10.1038/s41598-017-16034-9
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol modulates cocaine-induced inhibitory synaptic plasticity in VTA dopamine neurons by inhibiting phosphodiesterases (PDEs)

Abstract: Resveratrol is a natural phytoalexin synthesized by plants, including grapes. It displays a wide range of neuroprotective benefits associated with anti-aging. Recent studies have shown that resveratrol regulates dopaminergic transmission and behavioral effects of drugs of abuse. The goal of the present study is to investigate whether and how resveratrol alters basal inhibitory synaptic transmission and cocaine-induced inhibitory synaptic plasticity in dopamine neurons of the ventral tegmental area (VTA). We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(81 reference statements)
2
8
0
Order By: Relevance
“…Interestingly, acute RSV treatment enhanced cocaine-induced dopamine neurotransmission and behavioral responses suggesting that RSV promotes drug addiction [49,50]. However, RSV is also shown to protect against drug addiction through an unknown mechanism [51,52]. Consistent with the dichotomic effects discussed above, RSV protects against Wallerian degeneration [53], but it also abolishes neuroprotection mediated through Wallerian-slow degeneration mutants [25].…”
Section: Introductionmentioning
confidence: 66%
“…Interestingly, acute RSV treatment enhanced cocaine-induced dopamine neurotransmission and behavioral responses suggesting that RSV promotes drug addiction [49,50]. However, RSV is also shown to protect against drug addiction through an unknown mechanism [51,52]. Consistent with the dichotomic effects discussed above, RSV protects against Wallerian degeneration [53], but it also abolishes neuroprotection mediated through Wallerian-slow degeneration mutants [25].…”
Section: Introductionmentioning
confidence: 66%
“…Reversing maladaptive plasticity at inhibitory synapses holds potential for treating various neuropsychiatric disorders, including addiction, depression, and anxiety. While the translational relevance of this approach remains to be examined, an increasing number of studies show that pharmacologic targeting of inhibitory synaptic plasticity can prevent or block various aberrant behaviors in animal models of pathology [26, 31, 32, 59, 61, 64, 89]. A form of inhibitory plasticity that has gained increasing attention involves long-lasting alterations in the transmembrane Cl − gradient.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Several studies have mentioned the neurological role of resveratrol in depression and anxiety (Yu et al, 2013;Li et al, 2017) and the gut homeostasis-related role of resveratrol in stress-induced irritable bowel syndrome (Xu Y. et al, 2018).…”
Section: Resveratrol Contributes To the Gut-brain Axis By Involving 5-htmentioning
confidence: 99%
“…Bastien -Dionne et al, 2011;Daitoku et al, 2011;Dao et al, 2011;Lee et al, 2012Lee et al, , 2014Samson and Bajaj, 2013;Xu et al, 2014;Shi and Huang, 2018;Zhuang et al, 2019 Resveratrol and 5- HT Xu et al, 2010;Yu et al, 2013Yu et al, , 2019Enck et al, 2016;Li et al, 2017;Nabavi et al, 2017;Peng et al, 2018;Xu L. et al, 2018 Resveratrol and gut microbiota Dao et al, 2011;Wu et al, 2011;Amri et al, 2012;Rotches-Ribalta et al, 2012;Bode et al, 2013;Qiao et al, 2014;Hsieh et al, 2015;Basholli-Salihu et al, 2016;Ling et al, 2016;Bird et al, 2017;Carrera-Quintanar et al, 2018;Hu et al, 2019 Ripken et al suggested that serotonin treatment could boost GLP-1 release, and the blocking of 5-HT receptor could affect the production of GLP-1 (Ripken et al, 2016).…”
Section: Resveratrol and Glp-1mentioning
confidence: 99%